Disegni, bizze e fulmini. I racconti di Carlo Emilio Gadda e Frammenti e meraviglie. Gadda e i generi della prosa breve di Giuliano Cenati (ENTHYMEMA, 2011)
Review of two publications in which Giuliano Cenati investigates the fragmentary, oxymoronic, and metamorphic nature of Carlo Emilio Gadda’s short prose.